Trends in river total suspended sediments driven by dams and soil erosion: a comparison between the Yangtze and Mekong rivers - Guan, Qi (2023)
Global river systems are experiencing rapid changes in sediment transport under growing anthropogenic and climatic stresses. However, the response of sediment discharge to the coupled influence of anthropogenic and natural factors and the associated impacts on the fluvial geomorphology in the Yangtze and Mekong rivers are not comprehensively assessed. Here, we recalibrated a seamless retrieval algorithm of the total suspended sediment (TSS) concentrations using in situ data and concurrent satellite data sets to analyze spatiotemporal patterns of the TSS concentrations in the lower Yangtze and Mekong rivers. Combined with soil erosion rates estimated by the Revised Universal Soil Loss Equation for the past 20 years, we examined the contributions of different factors to TSS trends. The results show that TSS concentrations in the Yangtze River decreased from 0.47 g L−1 in 2000 to 0.23 g L−1 in 2018 due to the construction of the Three Gorges Dam (TGD), especially in the Jingjiang reach, with a declining magnitude of 0.3 g L−1 (∼56%) since the TGD began operating. The Mekong River experienced increasing TSS concentration trends upstream and decreasing trends downstream from 2000 to 2018, possibly attributed to increased upstream soil erosion and decreased downstream water discharge. Declining TSS concentrations in both rivers have driven varying degrees of river channel erosion over the past two decades. This study investigated long-term changes in the TSS concentrations and soil erosion in the Yangtze and Mekong rivers, and the results provide baseline information for the sustainable development of river sediment delivery.